Eosinophilic Granuloma in the Shaft of the Femur - Islam, Md Nazrul; Hasan, Suzon AL (TAJ: Journal of Teachers Association, 2011)
Eosinophilic granuloma, the mildest from of histiocytosis appears in children, adolescents and young adults, though most patients present before ten years of age and it may be solitary of multiple. Most of lesions appear in the flat bone, in skull or in vertebral body. It may cause collapse of vertebra, which is called Vertebral plana. Eosinophilic granuloma in the diaphysis of femur is not common; so we are encouraged to report the case. DOI: http://dx.doi.org/10.3329/taj.v14i2.8394 TAJ 2001; 14(2): 88-89